Meadow degradation in a rural community of a protected natural area - Castro Castillo, Teresita de Jesús; Pinto Ruiz, René; Guevara Hernández, Francisco; Raj Aryal, Deb; Camas Gómez, Robertony; Avelar Roblero, Juan Uriel (Revista Mexicana de Ciencias Agrícolas, 2022)
In order to know the degree of degradation of meadows, as well as the social perception on how to avoid it, in the rural community Francisco Villa I, municipality of Jiquipilas, Chiapas, located in the area of influence of the protected natural area La Sepultura Biosphere Reserve. Since no similar studies in the region were found, it was considered a challenge to evaluate the degradation of the meadow from the local perspective and compare it with the technical evaluation to perceive that strategies to avoid and stop it can arise from the social initiative. The management characteristics of grazing areas and the strategies that producers would employ to mitigate the degradation of their paddocks were determined through 11 semi-structured interviews. To evaluate the degree of degradation, a probabilistic sample was selected, from 10 plots divided according to the botanical composition, in two systems of grazing areas: the naturalized one and the improved one, variables: vegetation cover [double sampling or botanal method of Tothill et al. (1992)], botanical composition [double sampling technique described by Haydock and Shaw (1975)] and tree inventory (Dallmeier, 1992). The analysis was descriptive, except for the variable of Vegetation cover, of Tukey’s mean comparison (p> 0.05). Vegetation cover was higher (58%) for the naturalized grass system and lower (51.6%) for the improved one; the botanical composition was 37% of the Cynodon plectostachyus grass for the former and 34% of cover with the Andropogun gayanus grass in the latter, with 12 and 9 tree species, respectively. The level of degradation of the paddocks evaluated of the grazing areas was rated as moderate by the producers, coinciding with the technical results made.